Conflict transforming and religion : essays on faith, power and relationship - Marshall, Ellen Ott. (New Delhi : Palgrave MacMillan, 2016)
Writing from a variety of contexts, the contributors to this volume describe the ways that conflict and their efforts to engage it constructively shape their work in classrooms and communities.
Keywords: Religion; Conflict management; Religions -- Relations; Peace -- Religious aspects